Housing, Scarcity, and Vaulted Architecture in 1980s Syria - Al Asali, Wesam; Shahin, Iyas (European Architectural History Network (EAHN), 2026)
In the late 1980s, Syria’s architectural landscape underwent a pivotal transformation driven by the severe economic challenges resulting from sanctions and regional conflicts. The scarcity of imported materials, particularly steel, rendered conventional reinforced concrete construction prohibitively expensive. In response, Syrian builders and architects began to embrace traditional techniques and local materials, focusing on compression-only structures, barrel and cross vaults supported by load-bearing walls in particular. Beyond serving their technical function, these vaults became instrumental in affordable housing and contributed to a broader discourse on establishing a distinct architectural ‘identity’ for the country’s rural areas. This paper examines various projects, initiatives, and movements related to vaulted affordable housing in Syria within both regional and national contexts. The research draws on primary data, personal archives, and records from architects and engineers who participated in these projects between 1982 and 1995. One of the most significant of these initiatives was the Al-Sharqyat housing project in the western suburb of Damascus, leading to its institutionalisation and large-scale implementation. As a state-led endeavour by the newly formed Military Housing Establishment, Al-Sharqyat exemplified how scarcity pushed Syrian architects to move beyond standardised methods and instead adopt experimental building practices. This paper explores the factors that led to the inception of the Al-Sharqyat project, its subsequent challenges, and eventual failure, with a focus on the project’s urban, architectural, and construction dimensions. These vaulted houses, which once encapsulated the evolving expressions of late Syrian modernist architecture—an area of architectural history that remains relatively unexplored—are currently being transformed.
Keywords: 62 Ciencias de las Artes y las Letras::6201 Arquitectura; ODS 11 - Ciudades y comunidades sostenibles; Syria; gated community; vernacular architecture; housing; vaults; Hassan Fathy